Densification by Compaction as an Effective Low‐Cost Method to Attain a High Areal Lithium Storage Capacity in a CNT@Co3O4 Sponge. Issue 19 (23rd March 2018) - Chen, Yijun; Wang, Yunsong; Wang, Zhipeng; Zou, Mingchu; Zhang, Hui; Zhao, Wenqi; Yousaf, Muhammad; Yang, Liusi; Cao, Anyuan; Han, Ray P. S.
Abstract: Achieving a high areal capacity is essential for the transfer of outstanding laboratory electrode results to commercial applications and also to ensure there exists a capacity matched cathode and anode for a properly tuned battery. Despite intensive efforts, most electrode materials exhibit areal capacities lower than that of the graphite anodes (4 mA h cm −2 ). An effective and low‐cost approach is reported to attain a high areal capacity via an intense densification by compacting a porous carbon nanotube sponge grafted with Co3 O4 nanoparticles. The hybrid sponge can be compacted to a large degree (up to a tenfold densification) while still keeping its structural integrity and the 3D porous network. This method allows achieving a mass loading of up ‑to 14.3 mg cm −2 and an areal capacity of 12 mA h cm −2 (at a current density of 200 mA g −1 ) together with a gravimetric capacity of >800 mA h g −1 . This densification by compaction approach offers an effective and low‐cost strategy to develop high mass loading and areal capacity electrodes for practical energy storage systems. Abstract : An effective hybrid electrode consisting of Co3 O4 nanoparticles grafted on to a porous carbon nanotube sponge is reported. Due to the self‐preserving characteristic of the original 3D network structure, the hybrid sponge can be controllably compacted to acquire predefined areal mass loadings and thereby achieve a tunable areal lithium storage performance (up to 12.0 mA h cm −2 ).